PERSEPSI TERHADAP BERITA KRIMINAL DI TELEVISI YANG BERLEBIHAN DAPAT MENIMBULKAN KECEMASAN PADA SISWA SMP - ilmi, jamiatul (Jurnal Bimbingan dan Konseling Pandohop, 2023)
The purpose of this study was to determine the relationship between adolescents' perceptions of crime news on television and their anxiety from watching crime news on television. There were around 60 students from SMPN 3 Sijunjung who took part in this research. The independent variable is students' perception of crime news on television, while the dependent variable is students' anxiety from watching crime news on television. The r value of the Perception Scale ranges from 36-.75, while the r value for the Concern Scale ranges from 336-.764. Hypothesis analysis using product moment correlation showed that there was a significant relationship between students' perceptions of crime news on television and students' anxiety from watching crime news on television (r,.430, p P <.01). The contribution of the perception variable in influencing the anxiety variable is only 18.5%. Some recommendations for future research and explanations about other influencing variables outside of this research are discussed.